Strategic Development of Top Buah Segar: SWOT and Tows Matrix Analysis - Nugraha, Angga; Aldianto, Leo (Journal of Business and Management, 2012)
Nowadays, PeopleÃ¢â‚¬â„¢s paradigm has shifted from not only concern with low prices, but also concern with the pleasantness of a store or market. Modern people tend to go to modern market which is more comfortable compared to traditional market. Top Buah Segar is one example of the modern market. The tools used in this research were SWOT and TOWS Analysis,Ã‚Â and questionnaire. SWOT Analysis was used to identify the internal and external factors affected Top Buah Segar in the industry from the perception of the company itself. On the other hand, questionnaire which based on Marketing Mix 7P strategy identified the internal factors of firm from customersÃ¢â‚¬â„¢ perception.the researcher found strength, weaknesses, opportunities and threats of Top Buah Segar Bekasi. Top Buah Segar in Bekasi lack in almost every aspect of the Markting Mix 7p, while Top Buah Segar in Cibuburexcell at every aspect. In order to increase its performance the researcher recommend that Top Buah Segar Bekasi need to hire more employees to better manage the stores, create a marketing team to search and maintain customers, and they need to fix the physical evidence. Keywords : SWOT Analysis, Marketing Mix Category : Performance management, Marketing